Workplace Support and Service - Oriented Organisational Citizenship Behaviour: The Mediating Role Of Psychological Empowerment And Affective Commitment - Nguyen Le-Hoang Long; Nguyen Thi-Thu Huong; Ho Viet–Anh (Cogent Business & Management, 2022)
The purpose of this study is to examine the mechanism underpinning the relationship between perceived supervisor support, perceived organisational support, and service-oriented organisational citizenship behaviour. The data was collected from 250 flight attendants working in airline companies, and structural equation model modelling using M-plus 7.0 was employed to test the hypotheses. This research provides evidence for the association between psychological empowerment, affective commitment, and service-oriented organisational citizenship behaviour. Additionally, perceived organisational support, psychological empowerment, and affective commitment were found to mediate the relationship between employees' perceptions of the support from their supervisor and their service-oriented citizenship behaviour. In addition to contributing to the current literature, this research also suggests important implications for managers and practitioners in airlines.
Keywords: 650; affective commitment; aviation; perceived organisational support; perceived supervisor support; psychological empowerment; service-oriented OCB